(3GdMQcI GdhWfjI GdLRGFQjI (B/s - (3SYO Gddg , CHh GdbGSe s ((3GdLRGFQ (B:s (3GdeDSSI GdhWfjI ddcJGH(B;(3eWHYI GdfNdI ,s, 1992)
(3gPg JQLeI dGWQhMI GdOcJhQGg GdJj MUd HgG GdeDda Ydi GdOcJhQGg aj GdJGQjN h GdYdhe GdSjGSjI ef LGeYI ejfjShJG HCejQcGs
Keywords: (3GdLRGFQjI s; (3GdhWfjI s; (3GdMQcIs